Electron beam assisted recycling of polyurethane (PU) sponge: Turning it into a superabsorbent for wastewater treatment. Issue 9 (30th December 2022) - Jha, Atanu; Shaik, Khader Abdul; Bhardwaj, Yatender Kumar; Pant, Harish Jagat; Chowdhury, Subhendu Ray
Abstract: Polyurethane (PU) sponge is being used on a large scale now‐a‐days, but that generates environmental pollution as it is not bio‐degradable. Moreover, the PU recycling existing techniques face several problems, which are being addressed sincerely throughout the world. Here, we report an easy, scalable, environment‐friendly, economic, and high throughput technique for converting scrap PU sponge into a superabsorbent for wastewater treatment. This is a new strategy for recycling scrap PU foam. This conversion follows the modification of surface energy of the PU sponge and generation of tiny‐scale roughness by a single‐step electron beam (EB) radiation‐assisted covalent attachment of dodecyl methacrylate (DMA) onto the waste PU sponge. The effect of degree of modification on the surface wettability is studied. Important process parameters namely, total dose, DMA concentration, solvent composition, and so forth are systematically varied and optimized to achieve the required extent of modification (~30 wt%). This desired degree of modification is achieved at 30 kGy total dose and in 15 vol% DMA concentration and 15 vol% water content in the reaction mixture. Grafting yield is measured gravimetrically and successful grafting is further confirmed by Fourier‐transform infrared spectroscopy, surface wettability, and surface morphology. The recycled PU shows superhydrophobicity with very high water contact angle (152°). Now, the recycled sponge can remove major liquid components of wastewater, namely, toxic organic solvents, oily liquids, nonpolar solvent soluble dyes from water media with high absorption capacity (25–30 g/g) successfully. Abstract : Illustration of the conversion of polyurethane (PU) sponge into a superabsorbent.